Carbon management of commercial rangelands in Australia: Major pools and fluxes - Dean, Christopher; Wardell-Johnson, Grant; Harper, R. (Elsevier BV, 2012)
Land-use emissions accompanying biomass loss, change in soil organic carbon (ΔSOC) and decomposing wood-products, were comparable with fossil fuel emissions in the late 20th century. We examine the rates, magnitudes and uncertainties for major carbon (C) fluxes for rangelands due to commercial grazing and climate change in Australia. Total net C emission from biomass over 369 Mha of rangeland to-date was 0.73 (±0.40) Pg, with 83% of that from the potentially forested 53% of the rangelands. A higher emission estimate is likely from a higher resolution analysis. The total ΔSOC to-date was −0.16 (±0.05) Pg. Carbon emissions from all rangeland pools considered are currently 32 (±10) Tg yr−1—equivalent to 21 (±6)% of Australia's Kyoto-Protocol annual greenhouse gas emissions. The ΔSOC from erosion and deforestation was −4.0 (±1.6) Tg yr−1—less than annual emissions from livestock methane, or biomass attrition, however it will continue for several centuries. Apart from deforestation a foci of land degradation was riparian zones. Cessation of deforestation and onset of rehabilitation of degraded rangeland would allow SOC recovery.If extensive rehabilitation started in 2011 and erosion ceased in 2050 then a ΔSOC of −1.2 (±0.5) Pg would be avoided. The fastest sequestration option was maturation of regrowth forest in Queensland with a C flux of 0.36 (±0.18) Mg ha−1 yr−1 in biomass across 22.7 Mha for the next 50 yr; equivalent to ∼50% of national inventory agriculture emissions (as of mid 2011); and long-term sequestration would be 0.79 (±0.40) Pg. Due to change in water balance, temperature and accompanying fire and drought regimes from climate change, the forecast ΔSOC from the forested rangelands to 0.3 m depth was −1.8 (0.6) Pg (i.e. 38 (12)% of extant SOC stock) resulting from a change in biomass from 2000 to 2100. For improved management of rangeland carbon fluxes: (a) more information is needed on the location of land degradation, and the dynamics and spatial variation of the major carbon pools and fluxes; and (b) freer data transfer is needed between government departments, and to the scientific community.